NLRP3 inflammasome: A therapeutic option for kidney disease? (2017)
Objective To determine if considering inflammasome NLRP3 as a treatment option for kidney disease is possible.Methods Literature review related to NLRP3 inflammasome structure, biological function and relationship with renal disease and others (hypertension, diabetes, gout, atherosclerosis, amyloidosis, Alzheimer's disease); the systematic review was made searching in the databases PubMed and SciELO for the following terms: "The NLRP3 inflammasome therapeutic for kidney disease", "NLRP3 nflammasome in kidney disease" in PubMed, and "Inflammasome" for Scielo.Results 146 documents were found, althoughonly 34 matched the working hypothesis concerning the NLRP3 inflammasome as a central component of various diseases in humans, with potential therapeutic use. The NLRP3 inflammasome is responsible for the maturation of inflammatory pro-interleukin IL-1 β and IL-18, which can be triggered by aggregated or crystalline materials (particles), and by various microorganisms and toxins derived from these; however, the way how activation mechanisms work is not completely clear.Conclusions Research on new therapies that focus on removing or inhibiting inflammasome components, both individually and together, is proposed.